Lamento e luto na tradução de Suplicantes de Eurípides - Almeida, Vanessa Silva (2017)
This work aims at analyzing the mourning and funeral lamentations of the characters in Euripides’ Suppliants in the context of the Greek theater, religion and politics. For this, I propose the translation of the mentioned play into Brazilian Portuguese, observing throught it the way the aspects regarding to mourning in Ancient Greece can be comprehended by us. The proposed translation starts from the Greek text edition established by Paley (2010), and is supported by translations into modern languages, such as the Spanish one by José Luis Calvo Martínez (1995), the Brittish one by David Kovacs (1998), the Portuguese one by José Ribeiro Ferreira (2012), among others. The first chapter presents some general notions of Theater and discusses the theater translator’s role in light of these definitions; the second one regards more specifically to the Greek Theater itself; the third one brings the proposed translation with the notes and a brief presentation of the Suppliants; the fourth one presents the study of the play regarding to the characters’ actions in scenes of lamentations, mourning and funeral rituals in its theatrical, religious and political implications. In this chapter, I am mainly based on Lourax (1994), Alexiou (2002) and Storey (2008). Finally, I conclude with a reflection upon the translation process as well as the contribution of the translation of the play to the Classical and Translation Studies in Brazil